Mixing processes at the pycnocline and vertical nitrate supply: Consequences for the microbial food web in San Jorge Gulf, Argentina - Latorre, Maite Pilmayquen (2018)
Little is known about the base of the food web that could support the high productivity and marine biodiversity found in San Jorge Gulf, Patagonia, Argentina. Here we examine the key components of the microbial food web, including the standing stock and physiological state of the phytoplankton in the context of key oceanographic variables in the gulf. Water samples were collected at 16 stations for biological and chemical analyses, together with measurements of vertical structure and currents. The dynamics of the water column and its impact on nutrient availability for primary producers was evaluated. Our results show that, in spite of the observed low surface nutrient concentrations and low biomass, phytoplankton cells were in good physiological state. This is possible because nutrients are replenished at the pycnocline depth, as estimated by means of Richardson’s dynamic stability. Turbulence created by tides and the shear between overlapping water masses favors the disruption of the pycnocline. We suggest that, during summer, San Jorge Gulf maintains not only high primary productivity but also high phytoplankton biomass turnover rate, which is supported by a high C:N ratio, consistent with strong zooplankton grazing and export of organic carbon to deep waters.